Techno-economic evaluations: An innovative of hydraulic reaction turbine for pico-hydro generation system - Md Basar, Mohd Farriz; Mohd Rais, Nurul Ashikin; Abd Gani, Shamsul Fakhar; Mustafa, Wan Azani (Penerbit Akademia Baru, 2022)
The primary goal of this paper is to evaluate an innovative Z-Blade turbine technology and its potential implications for production costs and manufacturing techniques. From literatures, conventional pico-hydro technologies with a capability of less than 5kW are getting more and more attention as good alternatives to environmentally friendly power generation, but there are more expensive and complex for small power generation and small domestic consumer level. Therefore, a Z-Blade reaction turbine technical and environmental processes as well as financial research are described indepth. The methods for a Z-blade turbine design and implementation are described here, and also the material using for the Z-Blade turbine is a grey PVC pipe. Moreover, empirical description, designation, costing, and correlation are employed in the process of critically analysing the simple reaction water turbine novels. Also in this article, the manufacture of the Split Reaction Turbine (SRT) and Cross Pipe Turbine (CPT) was re-evaluated to take into consideration the technological and economic factors as well as the difficulties of both turbines. In the meantime, low-head, low-flow water resources used to examine additional features of Z-Blade. Theoretically, such a platform for hydro production is cost - effective and has a simplistic design methodology with a total cost of USD76 that equates to 7.6% of the overall installation cost and worthy of output up to 115W of mechanical energy.